Emily the criminal [videorecording (Blu-Ray)] - Ford, John Patton; Plaza, Aubrey, 1984-; Rossi, Theo, 1975-; Echikunwoke, Megalyn; Gershon, Gina (Vertical Entertainment, 2022)
Desperate for income, Emily takes a shady gig buying goods with stolen credit cards supplied by a charismatic middleman named Youcef. Seduced by the quick cash and illicit thrills, they hatch a plan to take their business to the next level.